Effect of parental background factors on reading habits of secondary school students in Ogun State, Nigeria (2015)
Purpose: This study was carried out to investigate the extent to which parental background factors predict reading habits among secondary school students in Ogun State, Nigeria. This is part of a larger study carried out to investigate factors predicting reading habits of secondary school students in Ogun State. Design/Methodology/Approach: The survey research design method of the correlational type was adopted for this study. Three specific objectives were set for the study while four research questions were answered. The multi-stage sampling technique was used to select a sample size of 595 senior secondary school two students to form the respondents for the study. The main instrument of data collection was the questionnaire designed by the researcher for the study. Five hundred and ninety five copies of questionnaire were distributed to the students out of which only 384 were returned with useful responses giving a response rate of 64.5%, The descriptive technique using frequency counts, percentages, mean scores and ranking as well as inferential technique of pearson product moment correlation were adopted for data analysis. Findings: The results of the study revealed that the secondary school students’ demonstrate high interest in reading as revealed by their keenness in reading and that the students read mainly for the purposes of passing examination, getting information, personal development, and knowledge acquisition. The results of the study also revealed that family income and father’s occupation are the only background factors that positively affect or influence reading habits of secondary school students. On the other hand, findings from the study revealed that background factors when taken together do not significantly jointly affect reading habits of students. Implication: In order to address the negative effects which parents’ occupation, educational level and family type are having on reading habits of students, it is suggested that government should provide a kind of safety nets through provision of monetary incentives to parents with low socio-economic status to enable them make provision for relevant reading materials for their wards/children. Originality/Value: It is, therefore, recommended that school libraries/school library media centres should be adequately stocked with relevant library and information resources to enable students from both high and low parental background have access to more library and information resources to improve their reading habits and ultimately bring about improved achievement in their academic endeavours.